Digital Commons as new Infrastructure: A new generation of public policy for digital transformation - Berlinguer, Marco (Umanistica Digitale, 2021)
Free and open source software (FOSS) has come to largely dominate software production. This means that the technology and industry leader of the digital revolution has integrated the digital commons into its core institutional arrangements. To understand the success trajectory of FOSS, however, it is necessary to rethink the initial approaches to the production logic behind it and this new generation of digital commons, recognizing the hybrid and multilayered nature of their governance. A rethink is equally necessary with regard to the public policies applied to FOSS, which have so far failed to successfully engage with these new systems of innovation and production. Especially since we are approaching a new phase of development of the FOSS ecosystem that will be characterized by a greater involvement of the public sector. A review of the notion of infrastructure and an analysis of the design principles emerging in the architecture of the latest generation of digital infrastructures, within which FOSS is increasingly intertwined with standards and modularity, may offer a new perspective to reconsider the construction and governance of these shared utilities and the role of public policy. Following this perspective, the intersection of standardization and FOSS can be identified as the terrain in which a new generation of public policy is most likely to be tested.